An Analysis of Discipline, Work Enthusiasm, and Work Motivation on Employee Performance - Sutoyo, Sutoyo; Koen Irianto Uripan; Sutomo, Sutomo; Rudiyanto, Rudiyanto (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of work discipline, work enthusiasm, and motivation on employee performance at PT. Sumber Djaja Perkasa. The research subjects included all 56 company employees, who were also used as research samples using a non-probability sampling technique. Data processing and analysis were performed using multiple linear regression with the assistance of IBM SPSS Statistics software version 25. Based on the analysis, it was found that individually (partially), the variables of work discipline, work enthusiasm, and motivation significantly influence employee performance. Simultaneously, these three variables also showed a significant influence on employee performance at PT. Sumber Djaja Perkasa.